The Cervicovaginal Expression Level of Interleukin-6 Can be a Prediction Factor for Cervical Intraepithelial Neoplasias and Cervical Cancer: A Prospective Cohort Study - Xiaolin Li; Xuehui Zhang; Yupeng Wang; Jing Li; Ying Guo; Li Zhao; Minxin Zhang; Ming Ji; Lizhi Zhang; Quanxin Qu; Fenge Li (Clinical and Experimental Obstetrics & Gynecology, 2023)
Background: The aim of this prospective study was to investigate the expression of interleukin-6 (IL-6) of cervicovaginal washings in cervical intraepithelial neoplasia (CIN) and cervical cancer, and to explore its value in predicting the treatment of CINs. Methods: Cervicovaginal washings were collected from of 200 patients from Tianjin First Central Hospital, who underwent colposcopy examination between March 2021 to March 2022. Those patients included 13 patients with cervical cancer, 33 patients with CIN3, 46 patients with CIN2, 76 patients with CIN1, and 32 with chronic cervicitis. IL-6 expressions of cervicovaginal washings were determined by enzyme-linked immuno-sorbent assay (ELISA), and other clinical records were obtained for analysis. Results: IL-6 expressions of the cervicovaginal washings in 5 groups of chronic cervicitis, CIN1, CIN2, CIN3, and cervical cancer group were 9.23 ± 11.30 pg/mL, 8.32 ± 12.18 pg/mL, 11.24 ± 24.61 pg/mL, 13.96 ± 23.19 pg/mL, and 71.53 ± 55.76 pg/mL, respectively. IL-6 expression in patients with cervical cancer were significantly higher than that in patients with chronic cervicitis and CIN1, 2, and 3 (p = 0.002, p = 0.003, p = 0.002, and p = 0.002, respectively). Particularly, IL-6 expression in CIN1, 2, 3, and cervical cancer is gradually increased which may be an indicator for CINs treatment. Besides, among 187 patients with high-risk human papillomavirus (HPV) infection, the IL-6 levels in HPV16/18 infection group and other high-risk HPV infection groups were 23.44 ± 43.33 ng/mL and 11.73 ± 23.37 ng/mL, which is statistically different (p = 0.043). Conclusions: IL-6 expression in cervicovaginal washings of CIN patients gradually increased suggesting that IL-6 may be involved in the whole process of cervical intraepithelial neoplasia developing into cervical cancer and can be a treatment biomarker for CINs.